2021
DOI: 10.3126/ajms.v12i12.39717
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin – The key model inflammatory marker in diabetic and non-diabetic COVID-19

Abstract: Background: Diabetics exhibit elevated serum ferritin level when compared to non-diabetic counterpart, indicates impact of its association with coronavirus disease 2019 (COVID-19) infection and disease progression. Ferritin is a key mediator of immune dysregulation through direct immunosuppression contributing to cytokine storm resulting in fatal outcome in COVID-19. Aims and Objectives: This study aims to estimate serum ferritin in diabetic (cases) and non-diabetic (controls) COVID-19 patients and its correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A study also suggested a positive correlation between HbA1c and serum ferritin (r=0.55, p <0.05) among diabetic COVID-19 patients. 41 Ferritin level was higher in the patients with HbA1c of >7.0% compared to those with HbA1c of 7.0% (p=0.011). High HbA1c was associated with decreased SpO2 (r=-0.78) and increased lung damage (r-0.66), ferritin (r=0.79), CRP (r=0.67), and D-dimer (r=0.60).…”
Section: Original Articlementioning
confidence: 87%
“…A study also suggested a positive correlation between HbA1c and serum ferritin (r=0.55, p <0.05) among diabetic COVID-19 patients. 41 Ferritin level was higher in the patients with HbA1c of >7.0% compared to those with HbA1c of 7.0% (p=0.011). High HbA1c was associated with decreased SpO2 (r=-0.78) and increased lung damage (r-0.66), ferritin (r=0.79), CRP (r=0.67), and D-dimer (r=0.60).…”
Section: Original Articlementioning
confidence: 87%
“…The high significant levels of serum ferritin were saw in poorly controlled diabetic COVID-19 cases in compare to well-controlled diabetic COVID-19 cases. Correlation analysis between cases of diabetic COVID-19 and non-diabetic COVID-19 controls indicates that serum ferritin level increases as the glucose level increases in the body [16].Diabetes and its associated with hyperferritinemia in the affected COVID-19 individuals will add to the problem. There are at least one underlying disorder (hypertension, diabetes, and chronic obstructive pulmonary disease) in severe cases compared to mild cases [17].Zhang et al, who shown that association of hyperglycemia without DM with a increase risk of critical care admission, mechanical ventilation, and death.…”
Section: Discussionmentioning
confidence: 99%
“…inflammatory cycle [8].The fatal outcomes by COVID-19 are accompanied by cytokine storm syndrome, thus the severity of disease dependent on the cytokine storm syndrome [3]. Several diabetes patients exhibit higher serum ferritin levels [14], and it is known that they face an elevated probability to experience serious complications from COVID-19 [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations